2021
DOI: 10.1007/s11250-021-02944-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metabolic syndromes and parasitic infection in Muscovy ducks under different management conditions

Abstract: Proper health management is essential for productivity in duck farming. However, there is limited information on the effect of management conditions on rates of metabolic problems and parasitic infections in anatids. We evaluated the rates of metabolic syndromes and gastrointestinal parasite involvement in Muscovy ducks up to 12 weeks of age, under 3 management conditions: backyard, organized, and organized with probiotics. Individuals under organized management developed 2 metabolic problems: ascites, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Angel wings not only affect their appearance, but also have a great impact on breeding, reproduction and commercial value. A recent study showed that nutrition and management have some effects on angel wing in ducks (Chavarro‐Tulcan et al, 2021). The goal of this study was to a perform case–control genome‐wide association study (GWAS) and genome‐wide selective sweep analysis to identify the genes and variations related to angel wings in Pekin ducks.…”
Section: Figurementioning
confidence: 99%
“…Angel wings not only affect their appearance, but also have a great impact on breeding, reproduction and commercial value. A recent study showed that nutrition and management have some effects on angel wing in ducks (Chavarro‐Tulcan et al, 2021). The goal of this study was to a perform case–control genome‐wide association study (GWAS) and genome‐wide selective sweep analysis to identify the genes and variations related to angel wings in Pekin ducks.…”
Section: Figurementioning
confidence: 99%